Move Analysis in Cinematic Conversations: Power and Fate in Final Destination 6: Bloodlines - Maulana, Alpin Agus; Purba, Dwi Rizky Oktavia; Nurhalizah, Siti; Rangkuti, Linda Astuti; Zulkarnain, Iskandar (EXCELLENCE: Journal of English and English Education, 2025)
This study examines the interaction structure in Final Destination 6: Bloodlines through move analysis, focusing on how dialogue reflects themes of fate and death. Centered on Stefani Reyes, a college student haunted by visions of a 1968 tragedy tied to her grandmother’s ability to prevent disaster, the film explores intergenerational trauma and determinism. Using a qualitative descriptive method and Halliday’s theory, the research identifies initiating, responding, and follow-up moves in character interactions. The findings show a dominance of initiating moves particularly statements and questions which highlight the characters’ struggle with a death curse. Responding and follow-up moves enhance emotional tension and interpersonal dynamics. The study concludes that move structure in the film not only drives communication but also deepens its philosophical exploration of fate versus free will. Keywords: Move, Final Destination 6, Film Dialogue